Canadian Residential Mortgage Markets : Boring But Effective? - Kiff, John. (Washington, D.C. : International Monetary Fund, 2009)
Klyuev (2008) concluded that the Canadian market for housing finance is highly advanced and sophisticated, but financing options were somewhat limited, particularly at terms longer than five years. This paper argues that the paucity of longer-term loans is caused by a five-year maturity cap on government-guaranteed deposit insurance, and a prepayment penalty limit on residential mortgage loans in the Interest Act. That said, the availability and cost of residential loans for prime borrowers are comparable to those in the United States.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet